Efficacy of good hygienic practices (GHPs) program of a food business operating inside a university in Quezon City - Montinola, Shella Ef-Em C.; Guevarra, Shirley P. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Abstract
Thesis (Master of Food Service Administration)--University of the Philippines Diliman
Keywords: Food handling -- Philippines -- Quezon City; Food handling -- Law and legislation -- Philippines -- Quezon City; Food service -- Sanitation -- Law and legislation -- Philippines -- Quezon City; College students -- Philippines -- Health and hygiene